Marriage Dispensation from the Perspective of Child Protection and Family Maslahah - Apriyanti; Eko Hidayat; Kartika (SMART: Journal of Sharia, Traditon, and Modernity, 2025)
This Marriage dispensation constitutes a legal instrument granted by the state as an exception to the statutory minimum age of marriage. In practice, however, its application continues to generate tensions between legal certainty, child protection, and the objective of establishing a family grounded in maslahah. This article aims to analyze marriage dispensation from the perspectives of child protection and family maslahah, positioning the best interest of the child as the primary guiding principle. The study employs a normative juridical method, using statutory and conceptual approaches through an examination of marriage legislation and child protection law. The findings indicate that marriage dispensation is frequently granted on the basis of short-term social and moral considerations, while insufficient attention is paid to the protection of children’s rights, psychological readiness, and the long-term implications for family resilience. From the perspective of maslahah, marriage dispensation should be directed toward preventing greater harm rather than generating new forms of vulnerability for children and families. This article emphasizes the need to strengthen judicial standards of assessment, enhance the involvement of psychologists and social workers, and promote preventive approaches through family and community education. When applied proportionately, marriage dispensation may function as a protective legal instrument rather than merely serving as a mechanism for legitimizing child marriage, thereby aligning with the objectives of child protection and the realization of a maslahah-oriented family.